The Role of Institution Building in Development Administration In Nigeria - Bello, Matthew Funsho; Adamu, Umar; Mackson, Abga Maina (NIU Journal of Social Sciences, 2023)
Institution building is a vital necessity for the sustenance of good governance and socio-economic growth and development. This is because institutions serve as viable channels through which the citizens express their expectations or dissatisfactions on any national issue. Moreover, they serve as effective means to establish political accountability; yet within the process of institutional development, there should be balanced development of the intuitions so that no particular institution becomes more powerful over other institutions. However, in recent years, in Nigeria there is a challenge of eroded institutions that has ultimately continued to grapple with emergent socio-economic and political challenges. This paper examines institution building as a strategy for sustainable growth and development in Nigeria, the objective is to explore the meaning of institution building and its role in achieving the desired national development and to identify the challenges militating against institution building in Nigeria. Findings from the study show that Nigeria’s institutions are generally weak and dysfunctional; persistently incapable of delivering on broad national goal of promoting growth and development. If we are to build institutions that will raise the quality of life of Nigerians, there should be policies that would result in institution building, that regulate the conduct of all in respect of institutional change and economic performance. The paper recommends that there must be political will towards implementing sound governmental policies and strengthening institutions that would make the citizens to have confidence in the leadership for stable political systems that would ensure economic prosperity and national security.   Keywords:  Development Administration, Institution Building, Political Systems, Sustainable Growth, Nigeria.